2013
DOI: 10.2754/avb201382010097
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem auditory evoked potentials in healthy cats recorded with surface electrodes

Abstract: The aim of this study was to evaluate the brainstem auditory evoked potentials of seven healthy cats, using surface electrodes. Latencies of waves I, III and V, and intervals I-III, I-V and III-V were recorded. Monaural and binaural stimulation of the cats were done with sounds ranging between 40 and 90 decibel Sound Pressure Level. All latencies were lower than those described in previous studies, where needle electrodes were used. In the case of binaural stimulation, latencies of waves III and V were greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 13 publications
1
8
1
Order By: Relevance
“…Our recorded latencies, amplitudes and the values of the intervals are lower than those described by Cauzinille (1997), probably as a consequence of using surface electrodes (Jost et al 1994;Musteață et al, 2013).…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Our recorded latencies, amplitudes and the values of the intervals are lower than those described by Cauzinille (1997), probably as a consequence of using surface electrodes (Jost et al 1994;Musteață et al, 2013).…”
Section: Discussioncontrasting
confidence: 46%
“…In another study done on animals with CVS, BAERs recorded with needle electrodes showed that there is an increase in central wave latencies comparing with the control (healthy) group (Steiss et al, 1994). Till now there are only few studies performed in animals using surface electrodes (Jost et al, 1994;Musteață et al, 2013). In those studies the wave's morphology was preserved but the latencies were lower than those previously obtained with needle electrodes (Steiss et al, 1994, Cauzinille, 1997.…”
Section: Introductionmentioning
confidence: 97%
“…The BAER test has been commonly used in evaluating the auditory function of animals and humans, being the only objective method that can provide the certain diagnosis of deafness (Wilson et al, 2006, Palumbo et al, 2014. Its advantages include being easy to perform, noninvasive, safe and cost-effective, compared with other objective measures of the auditory function.…”
mentioning
confidence: 99%
“…Impedance was kept below 5 Ω and alternating 0.1 ms click stimuli were applied through foam earphones inserted in each auditory canal. Stimulus intensity was set at 90 dB SPL; in monaural recording, the non-tested ear was masked by white noise with an intensity of 50 dB SPL to eliminate the crossover effect [6][7][8][9]. Each waveform resulted was an average of 1000 stimulations.…”
Section: Baer System and Electrodesmentioning
confidence: 99%
“…Audiogram testing uses different intensities for the auditive stimulus. For neurolocalization purposes, a standard intensity (e.g., 90 dB sound pressure level (SPL) [4][5][6][7]) is preferred. To present, in the absence of reference values, the electrical activity of these structures can only be interpreted by comparison with values obtained contralaterally.…”
Section: Introductionmentioning
confidence: 99%